2012
DOI: 10.1371/journal.pone.0041166
|View full text |Cite|
|
Sign up to set email alerts
|

Performance of the PointCare NOW System for CD4 Counting in HIV Patients Based on Five Independent Evaluations

Abstract: IntroductionPoint-of-care (POC) CD4 testing can improve access to treatment by enabling decentralization and reducing patient loss-to-follow-up. As new POC CD4 technologies become available, their performance should be assessed before widespread deployment. This study reports the findings of five independent evaluations of the PointCare NOW CD4 system.Materials/MethodsEvaluations were conducted in Southern Africa (Mozambique, South Africa) and North America (Canada, USA). 492 blood samples (55 from HIV-negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 17 publications
0
22
2
Order By: Relevance
“…In contrast with our 2011 study, an older 2009 study showed substantial bias for the PointCare NOW with central laboratory machines [14]. Our results suggest that improvements had been made in the PointCare NOW in the intervening time and should be noted.…”
Section: Classification Agreementcontrasting
confidence: 95%
See 1 more Smart Citation
“…In contrast with our 2011 study, an older 2009 study showed substantial bias for the PointCare NOW with central laboratory machines [14]. Our results suggest that improvements had been made in the PointCare NOW in the intervening time and should be noted.…”
Section: Classification Agreementcontrasting
confidence: 95%
“…Our study, where data was obtained in 2011, yielded systematic error, replicate precision, and enrollment classification results that were substantially better than those reported from a 2009 study [4] of the PointCare NOW machine. This suggested to us that improvements had occurred.…”
Section: Aimcontrasting
confidence: 58%
“…SWBPs tested on the PointCare Now platform in the “patient” mode were not measurable for percentage or absolute CD4 counts [16], thus testing on this platform was terminated at this stage of the study.…”
Section: Resultsmentioning
confidence: 99%
“…A peer-reviewed assessment of the Poincare NOW revealed low sensitivity; 53% and 61% of adult patients at the 350 and 200 cells/μL thresholds, respectively, were misclassified [34,46]. The CD4 POC PIMA analyzer (Alere, Inc.) evaluated in South Africa and in Zimbabwe, however, performed well compared to the standard protocol [33,35].…”
Section: Technologies For Disease Staging and Treatment Monitoring CDmentioning
confidence: 99%